Employee Information System Development at PT. Friends of Sakinah Flashlight Surabaya - Teguh Herlambang; Firman Yudianto; Mukhtar Adinugroho; Fajar Annas Susanto; Leni Yuliana (Utan Kayu Publishing, 2024)
PT Sahabat Sakinah senter is a service provider providing smart solutions, especially focusing on clearing in non-performing assets. We are committed to using information technology and algorithms to provide customers with quality non-performing asset collection strategies and resource pooling, as well as providing one-stop post-loan solutions. Our community service was carried out at PT Sahabat Sakina Center, a company engaged in billing customers who make online loans, where this company only accepts billing services. With the information system development training at PT Sahabat Sakinah Senter, it could modernizes its database and office systems.